Nature-Inspired Nanocomposites for Toxic Heavy Metals Removal: An Overview - Mudassar SanaUllah; Awais Ali Aslam; Abhishek Thakur; Sania Amjad; Shahzaib Ishfaq; Sadaf Ul Hassan; Usman Haidar; Muhammad Shahid Nazir; Mahmood Ahmed; Marek Kowalczuk (Reviews of Environmental Contamination and Toxicology, 2026)

Genome-wide study uncovering the role of GPAT gene family in watermelon and functional validation of ClGPAT8 against cold stress - Ali Aslam; Xiaomeng Wang; Muhammad Waseem; Muhammad Azam; Ashir Masroor; Qinghua Shi; Sher Muhammad; Aseel Smerat; Muhammad Khuram Razzaq; Ruimin Zhang (Plant Science, 2026)

From lake to plate: microplastic occurrence in freshwater fish and multi-index assessment of human exposure in Kaptai Lake, Bangladesh - Mohammed Manik; Md. Rashedul Haque; Md. Tauhid Hossain; Wahida Ahmed; Md. Rasheduzzaman; Md. Mostafizur Rahman; Muhammad Aslam Ali; Paolo Pastorino (Food Control, 2026)

Visual analytics of vaccine hesitancy: mapping sentiment and misinformation flows across digital ecosystems - Shahbaz Aslam; Sobia Abid; Arshad Ali; Babar Hussain; Muhammad Zahid Bilal (Next Research, 2026)

Genomic characterization of an isolate of tomato leaf curl New Delhi virus associated with tomato crops - Abdul Majid; Muhammad Taimoor Shakeel; Muhammad Naveed Aslam; Ambreen Maqsood; Muhammad Raheel; Waqas Ashraf; Tahir Farooq; Atta ur Rehman Khan; Mahmoud Ahmed Amer; Mohammed Ali Al-Saleh (European Journal of Plant Pathology, 2026)

Hyaluronic acid-functionalized liposomes as a nanoplatform for enhanced pharmacokinetics and therapeutic efficacy in arthritis - Zakir Ali; Muhammad Junaid; Sibgha Batool; Sidra Aslam; Tofeeq ur Rehman; Ali H. Alamri; Adel Al Fatease; Nabil K. Alruwaili; Majed A Alghamdi; Han-Gon Choi; Fakhar ud Din (Journal of Pharmaceutical Investigation, 2026)

Sustainable valorization of olive pomace industrial side stream via explainable machine learning guided biochar pyrolysis - Muhammad Ali Haider; Jawad Gul; Muhammad Nouman Aslam Khan; Dagmar Juchelkova (Process Safety and Environmental Protection, 2026)

Geochemical dynamics and risk assessment of multi-metal contamination in alluvial soil–rice ecosystems of Pakistan - Waqar Ali; Muhammad Shafeeque; Muhammad Salam; Kang Mao; Muhammad Wajahat Aslam; Hua Zhang; Wei Li (Journal of Environmental Chemical Engineering, 2026)

A comprehensive review on microplastics: Their presence in surface and ground water, environmental distribution, and impact on human and aquatic systems - Khashia Rashid; Shaukat Ali; Asif Hanif Chaudhry; Nosheen Sial; Muhammad Rizwan Akram; Muhammad Aslam (Science of The Total Environment, 2026)

Engineering active sites in binary PrCoO3/Mn2V2O7 heterointerface embedded in phosphorus-doped biochar for boosting pH universal water splitting - Sidra Aslam; Muhammad Safdar; Misbah Mirza; Yasir Abbas; Waseem Abbas; Basharat Ali (Fuel, 2026)

Arsenic speciation and biogeochemical cycling in Pakistan's alluvial rice ecosystem: Health and trade implications - Waqar Ali; Muhammad Shafeeque; Muhammad Salam; Kang Mao; Muhammad Wajahat Aslam; Sehrish Fatima; Hua Zhang; Wei Li (Environmental Pollution, 2026)

Tailoring of Cerium Oxide Nanosheets Having Superior Peroxidase Catalytic Activity for Colorimetric Detection of Hydrogen Peroxide - Mohib Ullah; Muhammad Aslam Khan; Sajid Ali; Asfandyar; Zeeshan Tahir; Muhammad Babar Saeed; Vineet Tirth; Ali Algahtani; Ruqia Nazir; Muslim Khan (Journal of Fluorescence, 2026)

Dual photo/electrocatalytic CO2 reduction by porphyrin based metal organic framework under visible light and electrochemical bias - Mamuna Aslam; Uzma Saleem; Ibrahim A. Shaaban; Tahani Rahil Aldhafeeri; Ataf Ali Altaf; Muzammil Iqbal; Muhammad Tariq; Mohammed A. Assiri; Shahid Hussain; Hafiz Muhammad Asif (Fuel, 2026)

Extended reduced versus full-dose treatment with factor Xa inhibitors in patients with venous thromboembolism: a GRADE-assessed systematic review and meta-analysis of randomized controlled trials - Umama Alam; Muhammad Abdullah Ali; Muhammad Ansab; Shree Rath; Fazia Khattak; Zaryab Bacha; Hafiza Tooba Siddiqui; Fatima Sajjad; Abdullah Afridi; Zarar Ahmad Khan Afridi; Osama Ahmad; Abdul Moiz; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Investigating the Wound Healing Potential of CuCO3 Nanoparticles in Alloxan-Induced Diabetic Albino Mice: An Experimental and In Silico Approach - Muhammad Saqib Rafiq; Jabbir Ali Khan; Ashfaq Ahmad Shah Bukhari; Samra Shafqat; Ahmad Waheed; Muhammad Yasir Abbas; Muhammad Waseem Aslam; Imran Ibrahim Shaikh; Khalid S. Almaary; Muhammad Saleem Khan (Biological Trace Element Research, 2025)

Phenotypic Plasticity of Safflower Genotypes in Response to Contrasting Climatic Conditions - Obaid Afzal; Mukhtar Ahmed; Sahir Hameed Khattak; Muhammad Aqeel Aslam; Saida Komal; Maryam Murtaza; Farrukh Bashir; Aqeel Ahmad; Aliya Mirbaz; Haroon Ur Rasheed; Ghulam Muhammad Ali; Muhammad Usman; et al. (Plant Molecular Biology Reporter, 2025)

Prevalence in Relation to Risk Factors of Babesia Bigemina in Bovines of Punjab (Pakistan) - Muhammad Wahab; Mian Abdul Hafeez; Faiza Aslam; Rimsha Farooq; Syeda Anam Sarwar; Waqas Ahmad; Liaqat Ali; Adeel Sattar; Waseem Khan (Acta Parasitologica, 2025)

Contamination and risk assessment of Thallium in the alluvial paddy rice soil system of Pakistan - Waqar Ali; Kang Mao; Muhammad Shafeeque; Muhammad Wajahat Aslam; Hua Zhang; Wei Li (Environmental Research, 2025)

Multicriteria evaluation of cropland suitability using multisource datasets of satellite remote sensing and ground observation - Danish Raza; Hong Shu; Sahar Mirza; Hasnat Aslam; Aqil Tariq; Rana Waqar Aslam; Hafsa Aeman; Muhsan Ehsan; Maryam Muhammad Ali (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

Bay leaves: the neuroprotective dietary spice via inhibition of amyloid-like aggregation - Nazish Mustafa; Sana Khan; Laila Anwar; Mir Muhammad Uzairullah; Huma Aslam Bhatti; Syed Abid Ali; Ghulam Abbas (Metabolic Brain Disease, 2025)

Managing water deficit in wheat through mulches and irrigation techniques in semi-arid regions - Salman Ahmad; Muhammad Aown Sammar Raza; Muhammad Ali; Rashid Iqbal; Muhammad Usman Aslam; Monika Toleikiene; Abd El-Zaher M. A. Mustafa; Humaira Rizwana; Imran Haider; Muhammad Zain; Saltanat Aghayeva; Ozhan Simsek; et al. (Cereal Research Communications, 2025)

Synthesis, Spectroscopic, Electronic and Molecular Docking Studies of Pyrazole Based Chalcones as Potential Anticancer Agents - Noreen Aslam; Muhammad Ibrahim; Afifa Yousuf; Muhammad Arif Ali; Jonathan M. White; Ansa Madeeha Zafar; Mussarat Jabeen; Misbahul Ain Khan (Journal of Fluorescence, 2025)

Efficacy of Flumetsulam for Post-Emergence Weed Management in Chickpea (Cicer Arietinum L.) Under the Semi-Arid Region of Pakistan - Muhammad Khuram Razzaq; Ali Aziz; Faisal Hayat; Muhammad Zia Ul Haq; Irfan Rasool; Muhammad Naveed Babur; Ali Aslam; Sher Muhammad; Ammara Tahir; Khalid Hussain (Journal of Crop Health, 2025)

Toxicity of Ethanolic Plant Extracts to Aphis gossypii, Bemisia tabaci, and Frankliniella occidentalis and Selectivity to Coccinella septempunctata and Menochilus sexmaculatus - Moazam Hyder; Faraz Ali; Muhammad Adeel Ghafar; Aslam Bukero; Inzamam ul Haq; Abdul Mubeen Lodhi; Youming Hou (Neotropical Entomology, 2025)

High-performance PVC/polyacrylate-graphene oxide membranes for Pb (II) and Hg (II) ion removal from polluted water: synthesis, characterization, and adsorption studies - Noreen Nasir; Junaid Raza; Abdul Hamid; Naseem Ahmad Khan; Mubushar Majeed; Muhammad Sohail Aslam; Anis Ali Shah; Muhammad Iftikhar; Bilal Arshad; Muhammad Sohail; Muhammad Saeed; Shifa Shaffique; et al. (Environmental Monitoring and Assessment, 2025)

Machine learning approach for photocatalysis: An experimentally validated case study of photocatalytic dye degradation - Hassan Ali; Muhammad Yasir; Hamza Ul Haq; Ali Can Guler; Milan Masar; Muhammad Nouman Aslam Khan; Michal Machovsky; Vladimir Sedlarik; Ivo Kuritka (Journal of Environmental Management, 2025)

Solvothermal synthesis of ruthenium doped MnV2O7@g-C3N4 nanocomposite for oxygen evolution reaction and high-performance asymmetric supercapacitors - Sidra Aslam; Muhammad Safdar; Sadia Akram; Muhammad Awais; Basharat Ali; Yasir Abbas; Waseem Abbas; Misbah Mirza (Journal of Environmental Chemical Engineering, 2025)

Effect of Phosphorus Modified Cotton Stick Biochar on Growth, Photosynthesis, Enzymatic Activities and Lead (Pb) Uptake in Tomato Plants Grown in Pb-contaminated Soil - Zaffar Malik; Aleena Shabir; Ahmad Ali; Muhammad Naveed Aslam; Humera Aziz; Syed Farhan Haider Bukhari; Sana Noreen; Usama Ali Tahir; Muhammad Rizwan (Journal of Soil Science and Plant Nutrition, 2025)

A review on hydrogen production using decorated metal-organic frameworks by electrocatalytic and photocatalytic water splitting - Rana Adeel Mehmood; Awais Ali Aslam; Muhammad Javid Iqbal; Ali Hamza Sajid; Ameer Hamza; Hina Fatima Tahira; Izaz Ul Islam; Erdal Yabalak (Fuel, 2025)

A multi-dimensional approach to assess crop mapping and farmer strategies in drylands of Bamyan, Afghanistan - Arnaud Caiserman; Sayed Muhammad Baqer Hussaini; Aslam Qadamov; Roy C. Sidle; Aziz Ali Khan (Agricultural Systems, 2025)

Impacts of climate change on Pakistan’s weather patterns: a comprehensive study of temperature and precipitation trends - Hafiza Nida; Muhammad Kashif; Azhar Ali Janjua; Muhammad Aslam; Kamil Shahzad Cheema; Sami Ullah (Environmental Monitoring and Assessment, 2025)

Coral diversity and abundance patterns at the West Coast of Sabah: a case study of Kota Kinabalu coral reefs - Khodzori Fikri Akmal; Nor’ashikin Aslam Zuhairi; Zepri Abdul Muhaimin; Zarinah Waheed; Muhammad Ali Syed Hussein; Gan Sze Hoon; Yee Tong Kiu; Khairul Hisham Hariz; Mazni Muhammad Addin; Siti Nur Hazwani Oslan (Community Ecology, 2025)

Eco-friendly herbicide tolerance in maize (Zea mays Linn.) using moringa (Moringa oleifera Lam.) leaf extract - Hameed Ullah Khan; Muhammad Mudasar Aslam; Tahir Iqbal; Amana Khatoon; Muhammad Jamil; Shafiq Ur Rehman; Muhammad Nauman Khan; Majid Iqbal; Alevcan Kaplan; Sarah Abdul Razak; Baber Ali; Muhammad Siddique Afridi; et al. (Acta Physiologiae Plantarum, 2025)

The rise of 4D printing Technology: 2D MXenes for different applications - Iftikhar Hussain; Karanpal Singh; B. Kalidasan; Mubasher Ali; Ke-Juan Meng; Muhammad Kashif Aslam; Sabarison Pandiyarajan; Sajjad Hussain; P. Rosaiah; Saood Ali; Ho-Chiao Chuang; Kaili Zhang (Chemical Engineering Journal, 2025)

The efficacy of egg albumin nanoparticles adjuvanted Clostridium perfringens type D toxoid vaccine in rabbits - Mehwish Saeed; Saad Zafar; Zarreen Sajjad; Rizwan Aslam; Sultan Ali; Muhammad Shahid Mahmood; Mueed Aayan; Maria Sophy; Saqib Umer; Sajjad Ur Rahman; Muhammad Naveed Anwar (Brazilian Journal of Microbiology, 2025)

Olive oil and castor oil-based self-nanoemulsifying drug delivery system of flurbiprofen can relieve peripheral pain and inflammation through reduction of oxidative stress and inflammatory biomarkers: a comprehensive formulation and pharmacological insights - Mazaghul Basar; Muhammad Imran Khan; Muhammad Furqan Akhtar; Fareeha Anwar; Ammara Saleem; Asadullah Madni; Zulcaif Ahmad; Ali Sharif; Bushra Akhtar; Uzma Shakoor; Aslam Khan (Inflammopharmacology, 2025)

Effect of Arsenic Exposure on AS3MT Protein Levels in Serum of Type 2 Diabetic Patients Compared to Non-diabetics - Saima Shokat; Riffat Iqbal; Muhammad Ahmed Ali; Atif Yaqub; Shaista Aslam; Samreen Riaz (Biological Trace Element Research, 2024)

Overview of industrial food fraud and authentication through chromatography technique and its impact on public health - Nabila Aslam; Rida Fatima; Ammar B. Altemimi; Talha Ahmad; Samran Khalid; Syed Ali Hassan; Rana Muhammad Aadil (Food Chemistry, 2024)

Identification of novel antimicrobial compounds in colostrum-associated Lactiplantibacillus plantarum ZFS 1 and 2 by integrating in vitro, machine learning and bioinformatics approaches - Zainab Fiaz; Fatima Noor; Aqsa Ikram; Talha Ali Chohan; Muhammad Zubair Aslam; Najma Arshad (Food Bioscience, 2024)

Polygonum bistorta Linn. as a green source for synthesis of biocompatible selenium nanoparticles with potent antimicrobial and antioxidant properties - Hafiz Abdul Haseeb; Muhammad Aslam Khan; Hassam Rasheed; Muhammad Usman Zahid; Thu Dung Doan; Muhammad Aamir Ramzan Siddique; Uzair Ahmad; Syed Ali Imran Bokhari (BioMetals, 2024)

Recent development towards the novel applications and future prospects for cellulose-metal organic framework hybrid materials: a review - Zeenat Qamar; Awais Ali Aslam; Farheen Fatima; Sadaf Ul Hassan; Muhammad Shahid Nazir; Zulfiqar Ali; Sameer Ahmed Awad; Aqeel Ahmad Khan (Environmental Science and Pollution Research, 2024)

Climate change impact on water scarcity in the Hub River Basin, Pakistan - Muhammad Nabeel Aslam; Saqib Ashraf; Sangam Shrestha; Mustajab Ali; Nguyen Cong Hanh (Groundwater for Sustainable Development, 2024)

Exploring fruit ripening methods: Conventional, artificial, and novel approaches for quality and health - Usama Nasir; Amir Ismail; Muhammad Riaz; Kashif Razzaq; Sajid Ali; Ajaz Hussain; Mavra Ameen; Asifa Saif; Farwa Aslam; Carlos Augusto Fernandes de Oliveira (Food Control, 2024)

Improving salinity tolerance in wheat plants via inoculation with Azospirillum brasilense and Bacillus subtilis for enhanced biomass, growth and physiological process - Nazish Aijaz; Muhammad Saqlain Zaheer; Akhtar Hameed; Hafiz M. Usman Aslam; Muhammad Waqar Alam; Hasan Riaz; Jayanthi Barasarathi; Saltanat Aghayeva; Rani Bibi; Muhammad Waheed Riaz; Hafiz Haider Ali; Salim Manoharadas; et al. (Acta Physiologiae Plantarum, 2024)

Surviving the desert's grasp: Decipherment phreatophyte Tamarix aphylla (L.) Karst. Adaptive strategies for arid resilience - Ummar Iqbal; Ali Daad; Ahmad Ali; Muhammad Faisal Gul; Muhammad Usama Aslam; Fahad Ur Rehman; Umar Farooq (Plant Science, 2024)

Prediction of surface urban heat island based on predicted consequences of urban sprawl using deep learning: A way forward for a sustainable environment - Shun Fu; Lufeng Wang; Umer Khalil; Ali Hassan Cheema; Israr Ullah; Bilal Aslam; Aqil Tariq; Muhammad Aslam; Saad S. Alarifi (Physics and Chemistry of the Earth, Parts A/B/C, 2024)

Evaluating satellite-based precipitation products for spatiotemporal drought analysis - Hussain Masood Khan; Muhammad Fahim Aslam; Muhammad Waseem; Hafiz Kamran Jalil Abbasi; Ali Iftikhar; Faraz Ul Haq (Journal of Arid Environments, 2024)

Revolutionizing soybean genomics: How CRISPR and advanced sequencing are unlocking new potential - Muhammad Khuram Razzaq; Muhammad Naveed Babur; Muhammad Jawad Akbar Awan; Ghulam Raza; Mehwish Mobeen; Ali Aslam; Kadambot H. M. Siddique (Functional & Integrative Genomics, 2024)

Antioxidant dimension and potential as bacterial growth inhibitors in crude extracts of two Artemisia species (Artemisia indica Willd. and Artemisia maritima L.) from Gilgit-Baltistan region, Pakistan - Hassam Rasheed; Adil Hussain; Muhammad Aslam Khan; Mujtaba Hassan; Syed Ali Imran Bokhari (Vegetos, 2024)

Low mercury risks in paddy soils across the Pakistan - Muhammad Wajahat Aslam; Bo Meng; Waqar Ali; Muhammad Mohsin Abrar; Mahmoud A. Abdelhafiz; Xinbin Feng (Science of The Total Environment, 2024)

Improving the efficiency of photovoltaic-thermoelectric generator system using novel flying squirrel search optimization algorithm: Hybrid renewable and thermal energy system (RTES) for electricity generation - Muhammad Yaqoob Javed; Aamer Bilal Asghar; Khazina Naveed; Ali Nasir; Basem Alamri; Muhammad Aslam; Essam A. Al-Ammar; Zsolt Conka (Process Safety and Environmental Protection, 2024)

Integrated study of GIS and Remote Sensing to identify potential sites for rainwater harvesting structures - Xingsheng Du; Aqil Tariq; Fakhrul Islam; Samman Aziz; Liaqat Ali Waseem; Muhammad Nasar Ahmad; Muhammad Amin; Naz Ul Amin; Shoaib Ali; Muhammad Aslam; Walid Soufan (Physics and Chemistry of the Earth, Parts A/B/C, 2024)

Assessment of heavy metals level in chicken with indeterminate analysis in localities of Lahore, Pakistan - Naveed Ahmad; Usama Afzal; Ramna Zafar; Muhammad Arslan; Saira Riaz; Shahzad Naseem; Muhammad Naeem; Adeena Fatima; Mubashar Ali; Muhammad Aslam (Environmental Monitoring and Assessment, 2024)

An appealing review of industrial and nutraceutical applications of pistachio waste - Syed Ali Hassan; Mueen Abbas; Sania Zia; Abid Aslam Maan; Muhammad Kashif Iqbal Khan; Abdo Hassoun; Aamir Shehzad; Richard Gattin; Rana Muhammad Aadil (Critical Reviews in Food Science and Nutrition, 2024)

Effects of selenium on biogeochemical cycles of cadmium in rice from flooded paddy soil systems in the alluvial Indus Valley of Pakistan - Waqar Ali; Kang Mao; Muhammad Shafeeque; Muhammad Wajahat Aslam; Wei Li (Science of The Total Environment, 2024)

Detection of high-risk human papillomavirus infected cervical biopsies samples by immunohistochemical expression of the p16 tumor marker - Muhammad Shafique; Iqra Shoaib; Bilal Aslam; Rabia Khalid; Imrana Tanvir; Muhammad Hidayat Rasool; Tawaf Ali Shah; Khalid S. Almaary; Mohammed Bourhia; Muhammad Usman Qamar (Archives of Microbiology, 2024)

Unraveling the defensive strategies of camel thorn Alhagi maurorum medik. For thriving in arid and semi-arid environments - Ummar Iqbal; Ahmad Ali; Ali Daad; Muhammad Usama Aslam; Fahad Ur Rehman; Umar Farooq; Muhammad Faisal Gul (Journal of Arid Environments, 2023)

Rainwater harvesting for agriculture development using multi-influence factor and fuzzy overlay techniques - Xiangtian Zheng; Abid Sarwar; Fakhrul Islam; Abdul Majid; Aqil Tariq; Muhammad Ali; Shazia Gulzar; Muhammad Ismail Khan; Muhammad Akmal Sardar Ali; Muhammad Israr; Ahsan Jamil; Muhammad Aslam; et al. (Environmental Research, 2023)

Utilization of cereal-based husks to achieve sustainable development goals: Treatment of wastewater, biofuels, and biodegradable packaging - Syed Ali Hassan; Mueen Abbas; Waqar Mujahid; Waqar Ahmed; Saeed Ahmad; Abid Aslam Maan; Aamir Shehzad; Zuhaib F. Bhat; Rana Muhammad Aadil (Trends in Food Science & Technology, 2023)

Cellulose-based adsorbent materials for water remediation: Harnessing their potential in heavy metals and dyes removal - Awais Ali Aslam; Sadaf Ul Hassan; Muhammad Haris Saeed; Osama Kokab; Zulfiqar Ali; Muhammad Shahid Nazir; Waleed Siddiqi; Aamir Ali Aslam (Journal of Cleaner Production, 2023)

Recent advances in biological hydrogen production from algal biomass: A comprehensive review - Ayesha Aslam; Ali Bahadar; Rabia Liaquat; Muhammad Muddasar (Fuel, 2023)

Evaluation of possible attenuative role of chrysoeriol against polyethylene microplastics instigated testicular damage: A biochemical, spermatogenic and histological study - Muhammad Umar Ijaz; Faria Saher; Nemra Aslam; Ali Hamza; Haseeb Anwar; Saad Alkahtani; Hammad Ahmad Khan; Mian Nadeem Riaz (Food and Chemical Toxicology, 2023)

An insight into the hepatoprotective role of Velpatasvir and Sofosbuvir per se and in combination against carbon tetrachloride-induced hepatic fibrosis in rats - Sadaf Yasmeen; Aslam Khan; Fareeha Anwar; Muhammad Furqan Akhtar; Sidra Yasmeen; Shafeeq Ali Shah (Environmental Science and Pollution Research, 2023)

The potential of functionalized graphene-based composites for removing heavy metals and organic pollutants - Muhammad Saqlain Iqbal; Awais Ali Aslam; Ramsha Iftikhar; Muhammad Junaid; Syed Muhammad Imran; Muhammad Shahid Nazir; Zulfiqar Ali; Muhammad Zafar; Ayesha Kanwal; Norinsan Kamil Othman; Ujjwal Pal; Ai Ling Pang; et al. (Journal of Water Process Engineering, 2023)

Pterostilbene reduces the progression of atopic dermatitis via modulating inflammatory and oxidative stress biomarkers in mice - Yasmin Bangash; Ammara Saleem; Muhammad Furqan Akhtar; Fareeha Anwar; Bushra Akhtar; Ali Sharif; Muhammad Imran Khan; Aslam Khan (Inflammopharmacology, 2023)

A review on covalent organic frameworks as adsorbents for organic pollutants - Awais Ali Aslam; Adnan Irshad; Muhammad Shahid Nazir; Muhammad Atif (Journal of Cleaner Production, 2023)

Effect of exogenous taurine on pea (Pisum sativum L.) plants under salinity and iron deficiency stress - Muhammad Arslan Ashraf; Rizwan Rasheed; Muhammad Rizwan; Iqbal Hussain; Ramish Aslam; Freeha Fatima Qureshi; Barira Shoukat Hafiza; Rohina Bashir; Shafaqat Ali (Environmental Research, 2023)

Production performance, protein digestibility, gut health and economic efficiency in sexed broilers with super dozing of lysine - Najam us Sahar; Muhammad Shoaib; Muhammad Aslam Mirza; Shaukat Ali Bhatti; Shahzad Ashraf; Noreen Aslam; Alishbah Roobi; Muhammad Arslan Asif (Tropical Animal Health and Production, 2023)

Prospects of antimicrobial peptides as an alternative to chemical preservatives for food safety - Iqra Kamal; Usman Ali Ashfaq; Sumreen Hayat; Bilal Aslam; Muhammad Hassan Sarfraz; Hamna Yaseen; Muhammad Shahid Riaz Rajoka; Asad Ali Shah; Mohsin Khurshid (Biotechnology Letters, 2023)

Haemodialysis alters the serum metal contents in chronic kidney failure patients at hyderabad and adjoining areas - Marvi Shaikh; Naseem Aslam Channa; Ali Muhammad Wahryah; Muhammad Haneef Mugheri; Shakil Samejo; Lubna Noorani (BioMetals, 2023)

Climate-induced optimal wheat cropping season and mapping districts vulnerabilities in Punjab, Pakistan - Azhar Ali Janjua; Muhammad Aslam (Environment, Development and Sustainability, 2023)

Applications of machine learning in thermochemical conversion of biomass-A review - Muzammil khan; Salman Raza Naqvi; Zahid Ullah; Syed Ali Ammar Taqvi; Muhammad Nouman Aslam Khan; Wasif Farooq; Muhammad Taqi Mehran; Dagmar Juchelková; Libor Štěpanec (Fuel, 2023)

Damage assessment of stored grain pests against rice grains types and wheat - Muhammad Waqar Hassan; Mohsin Ali Hashmi; Ghulam Sarwar; Zahid Mehmood; Warda Saleem; Muhammad Aslam Farooqi (International Journal of Tropical Insect Science, 2022)

A novel lens of stock market capitalization and environmental degradation - Aamir Azeem; Muhammad Akram Naseem; Naveed Ul Hassan; Ijaz Butt; Muhammad Toseef Aslam; Shahid Ali; Atif khan Jadoon (Environmental Science and Pollution Research, 2022)

Antidiarrheal and antispasmodic activities of Trillium govanianum rhizomes extract: involvement of calcium channel blockade - Naveed Muhammad; Shafiq Ur Rahman; Hilal Uddin; Omer Shehzad; Muhammad Ismail; Niaz Ali; Aslam Khan; Muhammad Shahid; Abid Ullah; Shujaat Ahmad; Haya Hussain; Ikram ul Haq; et al. (Natural Product Research, 2022)

Evaluation of insecticidal activity of Beauveria bassiana against different instar larvae of Plutella xylostella by using two different methods of application - Muhammad Shehzad; Muhammad Tariq; Qurban Ali; Asad Aslam; Tariq Mukhtar; Muhammad Faheem Akhtar; Asim Gulzar; Muhammad Faisal (International Journal of Tropical Insect Science, 2022)

Susceptibility of Helicoverpa armigera Hübner (Lepidoptera: Noctuidae) on detached plant parts of transgenic and non-transgenic cotton - Muhammad Jawad Saleem; Faisal Hafeez; Qurban Ali; Asad Aslam; Muhammad Arshad; Dilbar Hussain; Ayesha Iftikhar; Afifa Naeem; Muhammad Saleem (International Journal of Tropical Insect Science, 2022)

Bio-diesel production of sunflower through sulphur management in a semi-arid subtropical environment - Athar Mahmood; Masood Iqbal Awan; Sana Sadaf; Ahmed Mukhtar; Xiukang Wang; Sajid Fiaz; Sher Aslam Khan; Habib Ali; Faran Muhammad; Zafar Hayat; Farhana Gul; Shah Fahad (Environmental Science and Pollution Research, 2022)

Intron-containing hairpin RNA interference vector for OBP8 show promising mortality in peach potato aphid - Amber Afroz; Safeena Aslam; Umer Rashid; Muhammad Faheem Malik; Nadia Zeeshan; Muhammad Ramzan Khan; Muhammad Qasim Shahzad But; Sabaz Ali Khan (Plant Cell, Tissue and Organ Culture (PCTOC), 2022)

Lack of CpG islands in human unitary pseudogenes and its implication - Ammad Aslam Khan; Muhammad Shahryar Ali; Farah Babar; Anees Fatima; Muhammad Awais Shafqat; Bisma Asghar; Nimra Ilyas; Maheen Fatima; Ayesha Liaqat; Muhammad Aslam Gondal (Mammalian Genome, 2021)

Green Synthesis of Silver Nitrate Nanoparticles from Camelina Sativa (L.) and Its Effect to Control Insect Pests of Stored Grains - Habib ur Rehman; Beenish Majeed; Muhammad Aslam Farooqi; Amer Rasul; Muhammad Sagheer; Qurban Ali; Zunnu Raen Akhtar (International Journal of Tropical Insect Science, 2021)

Isolation of tyrosine derived phenolics and their possible beneficial role in anti-inflammatory and antioxidant potential of Tithonia tubaeformis - Noor Ul Ain Nawaz; Muhammad Saeed; Khalid Mohammed Khan; Irfan Ali; Huma Aslam Bhatti; Sabi-Ur-Rehman; Muhammad Shahid; Shaheen Faizi (Natural Product Research, 2021)

Paclobutrazol Improves Sesame Yield by Increasing Dry Matter Accumulation and Reducing Seed Shattering Under Rainfed Conditions - Muhammad Zeeshan Mehmood; Ghulam Qadir; Obaid Afzal; Atta Mohi Ud Din; Muhammad Ali Raza; Imran Khan; Muhammad Jawad Hassan; Samrah Afzal Awan; Shakeel Ahmad; Muhammad Ansar; Muhammad Aqeel Aslam; Mukhtar Ahmed (International Journal of Plant Production, 2021)
Several biotic and abiotic stresses significantly decrease the biomass accumulation and seed yield of sesame crops under rainfed areas. However, plant growth regulators (such as Paclobutrazol) can improve the total dry matter and seed production of the sesame crop. The effects of the paclobutrazol application on dry matter accumulation and seed yield had not been studied before in sesame under rainfed conditions. Therefore, a two-year field study during 2018 and 2019 was conducted with key objectives to assess the impacts of paclobutrazol on leaf greenness, leaf area, total dry matter production and partitioning, seed shattering, and seed yield of sesame. Two sesame cultivars (TS-5 and TS-3) were treated with four paclobutrazol concentrations (P0 = Control, P1 = 100 mg L −1 , P2 = 200 mg L −1 , P3 = 300 mg L −1 ). The experiment was executed in RCBD-factorial design with three replications. Compared with P0, treatment P3 improved the leaf greenness of sesame by 17%, 38%, and 60% at 45, 85, and 125 days after sowing, respectively. However, P3 treatment decreased the leaf area of sesame by 14% and 20% at 45 and 85 days after sowing than P0, respectively. Compared with P0, treatment P3 increased the leaf area by 46% at 125 days after sowing. On average, treatment P3 also improved the total biomass production by 21% and partitioning in roots, stems, leaves, capsules, and seeds by 23%, 19%, 23%, 22%, and 40%, respectively, in the whole growing seasons as compared to P0. Moreover, under P3 treatment, sesame attained the highest seed yield and lowest seed shattering by 27% and 30%, respectively, compared to P0. This study indicated that by applying the paclobutrazol concentration at the rate of 300 mg L −1 in sesame, the leaf greenness, leaf areas, biomass accumulation, partitioning, seed yield, and shatter resistance could be improved. Thus, the optimum paclobutrazol level could enhance the dry matter accumulation and seed production capacity of sesame by decreasing shattering losses under rainfed conditions.

The role of financial development indicators in sustainable development-environmental degradation nexus - Xiaolong Li; Zhiyuan Yu; Asma Salman; Qaisar Ali; Muhammad Hafeez; Muhammad Shoaib Aslam (Environmental Science and Pollution Research, 2021)

Can sulphur improve the nutrient uptake, partitioning, and seed yield of sesame? - Muhammad Zeeshan Mehmood; Obaid Afzal; Mukhtar Ahmed; Ghulam Qadir; Ahmed M.S. Kheir; Muhammad Aqeel Aslam; Atta Mohi Ud Din; Imran Khan; Muhammad Jawad Hassan; Tehseen Ahmad Meraj; Muhammad Ali Raza; Shakeel Ahmad (Arabian Journal of Geosciences, 2021)
Sulphur (S) is considered to improve the nutrient uptake of plants due to its synergistic relationship with other nutrients. This could ultimately enhance the seed yield of oilseed crops. However, there is limited quantitative information on nutrient uptake, distribution, and its associated impacts on seed yield of sesame under the S application. Thus, a two-year field study (2018 and 2019) was conducted to assess the impacts of different S treatments (S 0 = Control, S 20 = 20, S 40 = 40, and S 60 = 60 kg ha −1 ) on total dry matter production, nitrogen, phosphorus, potassium, S uptake and distribution at the mid-bloom stage and physiological maturity. Furthermore, treatment impacts were studied on the number of capsules per plant, number of seeds per capsule, thousand seed weight, and seed yield at physiological maturity in sesame. Compared to S 0 , over the years, treatment S 40 significantly increased the total uptake of nitrogen, phosphorus, potassium, and S (by 13, 22, 11% and 16%, respectively) at physiological maturity, while their distribution by 13, 36, 14, and 24% (in leaves), 12, 15, 11, and 15% (in stems), 15, 42, 18, and 10% (in capsules), and 14, 22, 9, and 15% (in seeds), respectively. Enhanced nutrient uptake and distribution in treatment S 40 improved the total biomass accumulation (by 28%) and distribution in leaves (by 34%), stems (by 27%), capsules (by 26%), and seeds (by 28%), at physiological maturity, as compared to S 0 . Treatment S 40 increased the number of capsules per plant (by 13%), number of seeds per capsule (by 11%), and thousand seed weight (by 6%), compared to S 0 . Furthermore, over the years, relative to control, sesame under S 40 had a higher seed yield by 28% and enhanced the net economic returns by 44%. Thus, our results suggest that optimum S level at the time of sowing improves the nutrient uptake and distribution during the plant lifecycle, which ultimately enhances total dry matter accumulation, seed yield, and net productivity of sesame.

Insights into the mechanisms of arsenic-selenium interactions and the associated toxicity in plants, animals, and humans: A critical review - Waqar Ali; Hua Zhang; Muhammad Junaid; Kang Mao; Nan Xu; Chuanyu Chang; Atta Rasool; Muhammad Wajahat Aslam; Jamshed Ali; Zhugen Yang (Critical Reviews in Environmental Science and Technology, 2021)

Heat stress in cultivated plants: nature, impact, mechanisms, and mitigation strategies—a review - Muhammad Umair Hassan; Muhammad Umer Chattha; Imran Khan; Muhammad Bilal Chattha; Lorenzo Barbanti; Muhammad Aamer; Muhammad Mehmood Iqbal; Muhammad Nawaz; Athar Mahmood; Abid Ali; Muhammad Talha Aslam (Plant Biosystems, 2021)

Appraisal of One Health approach amid COVID-19 and zoonotic pandemics: insights for policy decision - Muhammad Imran Arshad; Hilal Ahmad Khan; Bilal Aslam; Junaid Ali Khan (Tropical Animal Health and Production, 2021)

Carbon, nitrogen, and phosphorus stoichiometry mediate sensitivity of carbon stabilization mechanisms along with surface layers of a Mollisol after long-term fertilization in Northeast China - Muhammad Mohsin Abrar; Hu Xu; Tariq Aziz; Nan Sun; Adnan Mustafa; Muhammad Wajahat Aslam; Syed Atizaz Ali Shah; Khalid Mehmood; Baoku Zhou; Xingzhu Ma; Xianni Chen; Minggang Xu (Journal of Soils and Sediments, 2021)

First report of leaf spot of bottle gourd (Lagenaria siceraria) caused by Fusarium equiseti in Pakistan - Hafiz Muhammad Usman Aslam; Safdar Ali; Sabin Aslam; Muhammad Amjad Ali; Nasir Ahmad Khan; Yingyan Zhai; Mark L. Gleason (Journal of Plant Pathology, 2021)

Evaluating the relationship between climate variability and agricultural crops under indeterminacy - Azhar Ali Janjua; Muhammad Aslam; Naheed Sultana (Theoretical and Applied Climatology, 2020)

First report of brown leaf spot of rice caused by Curvularia spicifera in Pakistan - Hafiz Muhammad Usman Aslam; Safdar Ali; Muhammad Atiq; Muhammad Zeeshan Mansha; Hafiz Muhammad Aatif; Hafiz Arslan Anwaar; Khalid Naveed (Journal of Plant Pathology, 2020)

First report of Nigrospora sphaerica causing leaf spot of date palm in Pakistan - Muhammad Waqar Alam; Abdul Rehman; Shahbaz Ahmad; Mubeen Sarwar; Aamir Nawaz; Samiya Mahmood Khan; Sajid Ali; Sidra Aslam; Abdul Mannan (Journal of Plant Pathology, 2020)

Mixed matrix membranes incorporated with sonication-assisted ZIF-8 nanofillers for hazardous wastewater treatment - Mohsin Ali; Muhammad Aslam; Amin Khan; Mazhar Amjad Gilani; Asim Laeeq Khan (Environmental Science and Pollution Research, 2019)

Heat treatment effects on chilling injury and disease incidence in sweet orange fruits stored at chilling and non-chilling temperatures - Ijaz Hussain; Abdur Rab; Naqib Ullah Khan; Zarina Bibi; Shah Masaud Khan; Naushad Ali; Muhammad Saeed; Sher Aslam Khan; Sardar Ali; Ghulam Dastagir; Muhammad Sajid (Journal of Consumer Protection and Food Safety, 2019)

Unraveling prevalence and public health risks of arsenic, uranium and co-occurring trace metals in groundwater along riverine ecosystem in Sindh and Punjab, Pakistan - Waqar Ali; Muhammad Wajahat Aslam; Caiyan Feng; Muhammad Junaid; Kamran Ali; Shehong Li; Zhe Chen; Ziheng Yu; Atta Rasool; Hua Zhang (Environmental Geochemistry and Health, 2019)

A Review on the Status of Mercury Pollution in Pakistan: Sources and Impacts - Waqar Ali; Muhammad Junaid; Muhammad Wajahat Aslam; Kamran Ali; Atta Rasool; Hua Zhang (Archives of Environmental Contamination and Toxicology, 2019)

Genetic polymorphism in association with susceptibility to tuberculosis: a study in a Pakistani population - AsmaGul Naz; Muhammad Assad Aslam; Abrar Ul Haq Khan; Sumaira Rasul; Hamid Manzoor; Rehana Iqbal; Ahmed Shehzad; Muhammad Ali (Brazilian Journal of Microbiology, 2019)

First report of Alternaria alternata causing postharvest fruit rot of peach in Pakistan - Muhammad Waqar Alam; Abdul Rehman; Aman Ullah Malik; Sidra Aslam; Mubeen Sarwar; Sajid Ali; Muhammad Arslan Khan; Akhtar Hameed; Sohaib Sarfraz (Journal of Plant Pathology, 2019)

Effects of biochar on growth, photosynthesis, and chromium (Cr) uptake in Brassica rapa L. under Cr stress - Shafaqat Ali; Muhammad Rizwan; Ruqia Bano; Saima Aslam Bharwana; Muhammad Zia ur Rehman; Muhammad Bilal Hussain; Mohammad I. Al-Wabel (Arabian Journal of Geosciences, 2018)

Microfacies analysis and diagenetic fabric of the Lockhart Limestone exposed near Taxila, Margalla Hill Range, Punjab, Pakistan - Mohibullah Khan; Mumtaz Ali Khan; Birkhez Aslam Shami; Muhammad Awais (Arabian Journal of Geosciences, 2018)

Assessing the combined toxicity of conventional and newer insecticides on the cotton mealybug Phenacoccus solenopsis - Bushra Saddiq; Masood Ejaz; Sarfraz Ali Shad; Muhammad Aslam (Ecotoxicology, 2017)

Phenacyl group containing amide derivative of dehydroabietylamine exhibiting enhanced cytotoxic activity against PLC and MCF7 cancer cell lines - Muhammad Ayaz Mustufa; Afshan Aslam; Cigdem Ozen; Imran Ali Hashmi; Naim ul Hasan Naqvi; Mehmet Ozturk; Firdous Imran Ali (Medicinal Chemistry Research, 2017)

Physiological and biochemical mechanisms of silicon-induced copper stress tolerance in cotton (Gossypium hirsutum L.) - Shafaqat Ali; Muhammad Rizwan; Najeeb Ullah; Saima Aslam Bharwana; Muhammad Waseem; Muhammad Ahsan Farooq; Ghulam Hasan Abbasi; Mujahid Farid (Acta Physiologiae Plantarum, 2016)

Comparative Study of Physical Factors and Microbial Diversity of Four Man-Made Extreme Ecosystems - Imran Ali; Ali Akbar; Muhammad Aslam; Sami Ullah; Muhammad Anwar; Hunsa Punnapayak; Pongtharin Lotrakul; Sehanat Prasongsuk; Benjawan Yanwisetpakdee; Ponlada Permpornsakul; Sudip K. Rakshit (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2016)

Deltamethrin resistance in the cotton mealybug, Phenacoccus solenopsis Tinsley: Cross-resistance to other insecticides, fitness cost analysis and realized heritability - Bushra Saddiq; Naeem Abbas; Sarfraz Ali Shad; Muhammad Aslam; Muhammad Babar Shahzad Afzal (Phytoparasitica, 2016)

Mechanisms of silicon-mediated alleviation of drought and salt stress in plants: a review - Muhammad Rizwan; Shafaqat Ali; Muhammad Ibrahim; Mujahid Farid; Muhammad Adrees; Saima Aslam Bharwana; Muhammad Zia-ur-Rehman; Muhammad Farooq Qayyum; Farhat Abbas (Environmental Science and Pollution Research, 2015)

Citric acid enhances the phytoextraction of chromium, plant growth, and photosynthesis by alleviating the oxidative damages in Brassica napus L. - Sehar Afshan; Shafaqat Ali; Saima Aslam Bharwana; Muhammad Rizwan; Mujahid Farid; Farhat Abbas; Muhammad Ibrahim; Muhammad Aamer Mehmood; Ghulam Hasan Abbasi (Environmental Science and Pollution Research, 2015)

Fulvic acid mediates chromium (Cr) tolerance in wheat (Triticum aestivum L.) through lowering of Cr uptake and improved antioxidant defense system - Shafaqat Ali; Saima Aslam Bharwana; Muhammad Rizwan; Mujahid Farid; Sidra Kanwal; Qasim Ali; Muhammad Ibrahim; Rafaqat Ali Gill; Muhammad Daud Khan (Environmental Science and Pollution Research, 2015)

The effect of excess copper on growth and physiology of important food crops: a review - Muhammad Adrees; Shafaqat Ali; Muhammad Rizwan; Muhammad Ibrahim; Farhat Abbas; Mujahid Farid; Muhammad Zia-ur-Rehman; Muhammad Kashif Irshad; Saima Aslam Bharwana (Environmental Science and Pollution Research, 2015)

Methane flux from paddy vegetated soil: a comparison between biogas digested liquid and chemical fertilizer - Ankit Singla; Suresh Kumar Dubey; Muhammad Aslam Ali; Kazuyuki Inubushi (Wetlands Ecology and Management, 2015)

Contribution of greenhouse gas emissions during cropping and fallow seasons on total global warming potential in mono-rice paddy soils - Md. Mozammel Haque; Sang Yoon Kim; Muhammad Aslam Ali; Pil Joo Kim (Plant and Soil, 2015)

EDTA ameliorates phytoextraction of lead and plant growth by reducing morphological and biochemical injuries in Brassica napus L. under lead stress - Urooj Kanwal; Shafaqat Ali; Muhammad Bilal Shakoor; Mujahid Farid; Sabir Hussain; Tahira Yasmeen; Muhammad Adrees; Saima Aslam Bharwana; Farhat Abbas (Environmental Science and Pollution Research, 2014)

Synthesis, molecular docking and antiviral screening of novel N′-substitutedbenzylidene-2-(4-methyl-5,5-dioxido-3-phenylbenzo[e]pyrazolo[4,3-c][1,2]thiazin-1(4H)-yl)acetohydrazides - Sana Aslam; Matloob Ahmad; Muhammad Makshoof Athar; Usman Ali Ashfaq; John M. Gardiner; Catherine Montero; Mervi Detorio; Masood Parvez; Raymond F. Schinazi (Medicinal Chemistry Research, 2014)

Integrated effects of organic, inorganic and biological amendments on methane emission, soil quality and rice productivity in irrigated paddy ecosystem of Bangladesh: field study of two consecutive rice growing seasons - Muhammad Aslam Ali; M. A. Sattar; M. Nazmul Islam; K. Inubushi (Plant and Soil, 2014)

Hydrogen sulfide ameliorates lead-induced morphological, photosynthetic, oxidative damages and biochemical changes in cotton - Saima Aslam Bharwana; Shafaqat Ali; Muhammad Ahsan Farooq; Basharat Ali; Naeem Iqbal; Farhat Abbas; Muhammad Sajid Aqeel Ahmad (Environmental Science and Pollution Research, 2014)

Microsatellite analysis of Rosa damascena from Pakistan and Iran - Amjad Farooq; Mahnaz Kiani; Muhammad Aslam Khan; Atif Riaz; Asif Ali Khan; Natalie Anderson; David H. Byrne (Horticulture, Environment, and Biotechnology, 2013)

Mitigating Global Warming Potentials of Methane and Nitrous Oxide Gases from Rice Paddies under different irrigation regimes - Muhammad Aslam Ali; M. Anamul Hoque; Pil Joo Kim (Ambio, 2013)

Effect of silicate fertilizer on reducing methane emission during rice cultivation - Muhammad Aslam Ali; Chang Hoon Lee; Pil Joo Kim (Biology and Fertility of Soils, 2008)